BIOGEOCHEMICAL SILVER-DISPERSION HALOS OVER SILVER-ORE OCCURRENCES OF SIBERIA - Kovalevskiy A.L.; Kovalevskaya O.M. (My University, 1989)
Work done between 1978 and 1985 on shows with high-grade silver-ore bodies revealed over 10 new barrier-free plant substances - the wood of 'old', including rotted stumps of Scotch pine, Dahurian and Siberian larch, Siberian cedar, Siberian fir, spruce and various species of mushrooms. We also found that corky Scotch pine cones and aspen wood are highly informative and virtually barrier free with respect to silver. The data indicate that individual silver-ore veins can be found and outlined from barrier-free or virtually barrier-free plant species and parts alone. The best studied plant substance that is barrier free with respect to silver is wood of 'old', including rotted, Scotch pine stumps, whose silver content over such veins reaches 0.03 to 0.3 percent as compared with a background level ranging from 0.3 to 3 ppm and averaging about 1 ppm. Therefore, given that silver in plants is a universal indicator of metallic and some nonmetallic mineral resources, it should be included in the list of analyzed elements wherever the sampled plant species and parts are informative in terms of silver.